HUBUNGAN PENGAWASAN MINUM OBAT DENGAN KEBERHASILAN PENGOBATAN TB PARU PADA PASIEN DI WILAYAH KERJA PUSKESMAS TANAH LUAS KECAMATAN TANAH LUAS KABUPATEN ACEH UTARA TAHUN 2020 - Saragih, Elviana (Jurnal Kajian Kesehatan Masyarakat, 2021)
Pulmonary tuberculosis (Tb Lung) is one of the infectious diseases with the highest prevalence in the world. One of the factors that can influence the success of TB treatment, among others, the Regulatory of Take Medication is that taking Regulatory of Take Medication but less monitoring.The aim of this is to analyze the relationship between Regulatory of Take Medication the success of pulmonary TB treatment in the working area of ​​Tanah Luas Community Health Center in North Aceh Regency in 2020, with the type of survey with explanatory research type. which is in the working area of ​​the Tanah Luas Community Health Center. Sampling technique used purposive sampling with a sample size of 65 respondents. Data collection was questionnaire. Data analysis was performed univariate, bivariate with Chi-square test at 95% confidence level, α = 5% and multivariate with multiple logistic regression.The results of the analysis show that there is a relationship between education, knowledge and Regulatory of Take Medication with the success of the treatment of Tb Lung with each value p value = 0.003 <p = 0.05, knowledge p value = 0.005 <p = 0.05, the supervisor takes drugs = 0.019 <p = 0.05. The most dominant variable related is knowledge (B = 21.784).The management of the Tanah Luas Community Health Center can increase knowledge and implement Regulatory of Take Medication for patients with Tb Lung in order to increase success in the treatment of Tb Lung.